PENGGUNAAN MATRIKS PENDUKUNG (SILIKA GEL) PADA TANAMAN KAYU APU (pistia stratiotes. l) SEBAGAI BIOSORBEN UNTUK MENGURANGI TINGKAT PENCEMAR ION TIMBAL (Pb2+) - Sri Haryati; Elva Yasmi; Erviyenni - (Jurnal Riset Kimia, 2010)
Â ABSTRACTÂ ProblemsÂ ofÂ environmentalÂ becameÂ oneÂ ofÂ problemÂ mustÂ beÂ interestedÂ byÂ public,Â OneÂ ofÂ themÂ wasÂ theÂ stainÂ byÂ ionÂ leadÂ (Pb2+).Â AnÂ experimentÂ wasÂ conductÂ aboutÂ theÂ useÂ ofÂ â€œKayuÂ Apuâ€Â (PistiaÂ Stratiotes.Â L)Â asÂ ionÂ Pb2+Â adsorbentsÂ beforeÂ andÂ afterÂ addedÂ supportingÂ matrixÂ (silicaÂ gel).Â ThisÂ experimentÂ workedÂ withÂ staticÂ method.Â TheÂ parametersÂ wereÂ examinedÂ carefully:Â pHÂ (2,Â 4,Â 6,Â 8,Â andÂ 10),Â concentrateÂ (10,Â 25,Â 50,Â 75,Â andÂ 100Â ppm),Â andÂ contactedÂ timeÂ (15,Â 30,Â 45,Â 60,Â andÂ 75Â minutes).Â pH,Â concentrate,Â andÂ contactedÂ timeÂ optimumÂ forÂ â€œKayuÂ Apuâ€Â beforeÂ usingÂ supportingÂ matrixÂ (silicaÂ gel)Â successivelyÂ 6,Â 50Â ppm,Â 30Â minute,Â withÂ theÂ adsorbtionÂ efficiency:Â 89.16%.Â Besides,Â pH,Â concentrate,Â andÂ contactedÂ timeÂ optimumÂ afterÂ usingÂ supportingÂ matrixÂ (silicaÂ gel)Â successivelyÂ 4,Â 50Â ppm,Â 45Â minute,Â withÂ theÂ adsorbtionÂ efficiency:Â 97.47%.Â BiomaterialÂ ofÂ â€œKayuÂ Apuâ€Â hasÂ beenÂ givenÂ supportingÂ matrixÂ (silicaÂ gel)Â moreÂ efficientlyÂ thanÂ withoutÂ supporterÂ matrixsÂ forÂ adsorbingÂ ionÂ Pb2+.Keywords:Â pistiaÂ Stratiotes.Â L,Â biosorbent,Â silicaÂ gel,Â Pb2+